ALAT BATU DI PEGUNUNGAN TENGAH PAPUA - Marlin Tolla (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2011)
The discovery of stone tools in prehistoric sites in the central highlands of Papua, especially in the Pegunungan Bintang and Jayawijaya show about prehistoric evidence of human culture in the past. Besides the presence of lytic tool is supported also by the availability of materials, such as in the Pegunungan Bintang and Jayawijaya are very rich in various types of rocks, especially sedimentary rocks such as limestone and chert, and other types of igneous rocks such as andesite. This is makes it possible for human in the past in making stone tools used in their various activities such as hunting and gathering food.